2001
DOI: 10.1007/s002640000202
|View full text |Cite
|
Sign up to set email alerts
|

Non-operative treatment of multidirectional shoulder instability

Abstract: At an average follow-up of 3.7 years we assessed the results of non-operative treatment of 84 symptomatic shoulders in 59 patients with a diagnosis of multidirectional shoulder instability. Sixty-two shoulders had received no previous surgical treatment (group A) while 22 had failed to respond to surgical treatment before the rehabilitation programme (group B).Subjectively 11 of the non-operated shoulders (group A) were cured and 27 improved, 23 of the shoulders remained the same and one was worse at follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
92
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(103 citation statements)
references
References 16 publications
7
92
0
2
Order By: Relevance
“…In case of failure, surgical treatment, such as shoulder arthroscopy, is recommended [6]. Arthroscopic techniques have been used to treat the problems successfully for many years.…”
Section: Introductionmentioning
confidence: 99%
“…In case of failure, surgical treatment, such as shoulder arthroscopy, is recommended [6]. Arthroscopic techniques have been used to treat the problems successfully for many years.…”
Section: Introductionmentioning
confidence: 99%
“…The measurement was performed at the Biomechanical Laboratory of the Department of Applied Mechanics at the Budapest University of Technology and Economics, and Szolnok Hospital of Hungarian Railways. The detailed ultrasound-based shoulder kinematic and electromyographic measurement method is described by the same authors previously 8,9 .…”
Section: Methods Of Biomechanic Measurementmentioning
confidence: 99%
“…Several studies showed variable results with success rates between 30 and 80% (41)(42)(43). Surgical treatment should be considered after failure of conservative treatment or in the presence of bony abnormalities.…”
Section: J Ointsmentioning
confidence: 99%